Acoustic Emission Methodology and Application - Nazarchuk, Zinoviy; Skalskyi, Valentyn; Serhiyenko, Oleh (Foundations of Engineering Mechanics, 2017)
This monograph analyses in detail the physical aspects of the elastic waves radiation during deformation or fracture of materials. I presents the  methodological bases for the practical use of acoustic emission device, and describes the results of theoretical and experimental researches of evaluation of the crack growth resistance of materials, selection of the useful AE signals. The efficiency of this methodology is shown through the diagnostics of various-purpose industrial objects. The authors obtain results of experimental researches with the help of the new methods and facilities.